Proportionate response to the COVID‐19 threat? Use of apps and other technologies for monitoring employees under the European Union's data protection framework. - SUDER, Seili; SIIBAK, Andra (International Labour Review, 2022)
This article explores the potential uses by employers of contact‐tracing apps and other monitoring technologies to mitigate the spread of COVID‐19, and the potential concerns that these raise in the context of the European Union's General Data Protection Regulation. Given the imbalance of power in the employment relationship, the authors call for national laws to strengthen employees' ability to refuse the use of such apps and technologies after the end of the COVID‐19 pandemic. When such tools are no longer needed to keep employees safe, additional regulations and guidance will be necessary to prevent future problems, such as function creep and other misuse by employers.